Controlling the Dominant Length Scale of Liquid–Liquid Phase Separation in Spin‐coated Organic Semiconductor Films. (1st December 2014) - van Franeker, Jacobus J.; Westhoff, Daniel; Turbiez, Mathieu; Wienk, Martijn M.; Schmidt, Volker; Janssen, René A. J.
Abstract : Organic electronic devices are often made by solution processing a multi‐component ink. During solution processing, for example, via spin coating, the solvent evaporates and the solid components deposit on the substrate. The morphology of this layer can range from well‐mixed to extensively phase separated. To optimize device performance, it is essential to control the degree and dominant length scale of phase separation. Currently, the mechanism of phase separation induced by solvent evaporation is poorly understood. It has been shown that length scales are influenced by spin speed, drying time, final layer thickness and the ratio between the solid components, but a complete experimental dataset and consistent theoretical understanding are lacking. In this contribution, in situ measurements during spin coating and a simple numerical model are used to understand the drying process. In addition, an advanced image analysis of transmission electron micrographs of films processed under a wide range of processing conditions is carried out. A normalized drying rate is proposed as the key parameter that controls the dominant length scale of phase separation. Abstract : Droplet formation occurs in many solution‐processed organic semiconductor blends due to liquid–liquid phase separation. The combination of in situ measurements, a simple numerical spin coating model, and advanced image analysis on transmission electron micrographs show that the dominant length scale scales with a normalized drying rate, which is defined as the solvent evaporation rate divided by the dry layer thickness.